Translation purposes determine everything? appellation translation in Northern Shaanxi folk songs based on corpus method - Lin, Yan; Abdul Halim, Hazlina; Mohd Jalis, Farhana Muslim (Sciedu Press, 2023)
This study employs the skopos theory to analyze the translation methods used for appellations in Northern Shaanxi folk songs, a prominent genre in Chinese folk songs. The skopos theory emphasizes the importance of understanding and respecting the purpose of a translation, as it ultimately shapes the translation process and outcome. The English translations by Wang Hongyin and Wang Zhanbin are used to create a bilingual Chinese-English parallel corpus using a corpus technique. Additionally, to help the corpus software retrieve important statistics, the appellations and translation methods are manually annotated with the pertinent software. This study identifies seven primary categories of appellations, including those related to love, characters, laborers, family, mythology, allusions, and Buddhist figures. It explores the translation methods applied to each category, revealing that Wang Hongyin and Wang Zhanbin creatively adapt these appellations to convey their essence and significance to English-speaking readers while adhering to the skopos theorys principles. This article contributes valuable insights into the translation of Northern Shaanxi folk songs, transcending cultural boundaries and enhancing cross-cultural understanding.